STRUKTUR KERAGAAN EKONOMI PADA INDUSTRI ROKOK KRETEK DI INDONESIA : SUATU STUDI PUSTAKA - Suharyono Suharyono (Jurnal Ilmu dan Budaya, 2015)
Keragaan analysis of economics structure to industry smoke in Indonesia indicate that this industry have given constribute which good signifikan as spillway peacemaker of absorbtion of labour and also as one of the source of acceptance of state from within country. But that way affect cigarette to environment and health require to get serious attention. Cigarette industry have request price elasticity which is in elastic, market structure which is oligopoly, good pursuant to consentration ratio and also of Herfindahl Index. Characteristic product at industry smoke is heterogeneous, and also the existence of industrial kluster in unlucky and holy enable the existence of production efficiency. New entry barrier represent one of the characteristic found on industry smoke in Indonesia.